Lithium Chloride Exerts Differential Effects on Dentinogenesis and Osteogenesis in Primary Pulp Cultures - Vijaykumar, Anushree; Mina, Mina (Frontiers in Dental Medicine, 2021)
Wnt/-catenin signaling is known to play essential roles in odontoblast differentiation and reparative dentin formation. Various Wnt activators including LiCl have been increasingly studied for their effectiveness to induce repair of the dentin-pulp complex. LiCl is a simple salt thought to activate Wnt/-catenin signaling by inhibiting GSK3. Previous in vitro and in vivo studies showed that LiCl increased odontoblast differentiation and enhanced reparative dentin formation. However, the underlying molecular and cellular mechanisms by which LiCl regulates odontoblast and osteoblast differentiation during reparative dentinogenesis are not well understood. Our in vitro studies show that exposure of early dental pulp progenitors to LiCl increased the survival and the pool of SMA+ progenitors, leading to enhanced odontoblast and osteoblast differentiation. The positive effects of LiCl in the differentiation of osteoblasts and odontoblasts from SMA+ progenitors are mediated by Wnt/β-catenin signaling. Our results also showed that continuous and late exposure of dental pulp cells to LiCl increased the expression of odontoblast markers through Wnt/β-catenin signaling, and the number of odontoblasts expressing DMP1-Cherry and DSPP-Cerulean transgenes. However, unlike the early treatment, both continuous and late treatments decreased the expression of Bsp and the expression of BSP-GFPtpz transgene. These observations suggest that prolonged treatment with LiCl in more mature cells of the dental pulp has an inhibitory effect on osteoblast differentiation. The inhibitory effects of LiCl on osteogenesis and Bsp were not mediated through Wnt/β-catenin signaling. These observations suggest that the effects of LiCl, and GSK3 antagonists on reparative.